Coproducing healthcare service improvement for people with common mental health disorders including psychotic experiences: a study protocol of a multiperspective qualitative study - Alexandros Georgiadis; Robbie Duschinsky; Jesus Perez; Peter B Jones; Debra Russo; Clare Knight; Emma Soneson; Mary Dixon-Woods (BMJ Open)
Introduction Some people, who have common mental health disorders such as depression and anxiety, also have some psychotic experiences. These individuals may experience a treatment gap: their symptoms neither reach the increasingly high threshold for secondary care, nor do they receive full benefit from current interventions offered by the Improving Access to Psychological Therapies (IAPT) programme. The result may be poorer clinical and functional outcomes. A new talking therapy could potentially benefit this group. Informed by principles of coproduction, this study will seek the views of service users and staff to inform the design and development of such a therapy.Methods and analysis Semistructured interviews will be conducted with IAPT service users, therapists and managers based in three different geographical areas in England. Our sample will include (1) approximately 15 service users who will be receiving therapy or will have completed therapy at the time of recruitment, (2) approximately 15 service users who initiated treatment but withdrew, (3) approximately 15 therapists each with at least 4-month experience in a step-3 IAPT setting and (4) three IAPT managers. Data analysis will be based on the constant comparative method.Ethics and dissemination The study has been approved by the London Harrow Research Ethics Committee (reference: 18/LO/0642), and all National Health Service Trusts have granted permissions to conduct the study. Findings will be published in peer-reviewed academic journals, and presented at academic conferences. We will also produce a ‘digest’ summary of the findings, which will be accessible, visual and freely available.